Acidentes com instrumentos perfurocortantes entre cirurgiões-dentistas de Montes Claros, Brasil (Arquivos em Odontologia, 2016)
Percutaneous injuries are a common problem among dentists, who are among the healthcare professionals most involved in occupational accidents. This study evaluated the prevalence and characteristics of needlestick and sharp instrument injuries and the factors associated with these accidents among dentists. Structured, self-administered questionnaires were distributed to all dentists currently working in Montes Claros, Brazil. Percutaneous injuries within the previous six months and during the course of professional life were reported by 19.1% and 81.3%, respectively. The instrument most frequently mentioned was the bur, and injuries involved the finger; 56.3% reported the presence of bleeding, while 51.5% reported a compliance with the post-exposure protocol. Associated factors included sex, age, marital status, consumers of alcohol, hours worked per day, the use of gloves and mask 100% of the time, report of breaks taken during working hours, and knowledge about the post-exposure protocol. A higher prevalence of accidents occurred among dentists who were women, who were older aged, who drank alcohol, and who were unmarried. The list also included those who worked longer than 8 hours per day, did not take breaks during working hours, used masks 100% of the time, did not wear gloves all the time, and did not know the Brazilian post-exposure protocol.